[2+2] Photocycloaddition of 3-Alkoxycoumarins with C60 - Ueda, Mitsuhiro; Hayama, Miho; Hashishita, Hiroyuki (Synlett, 2019)
The [2+2] cycloaddition of 3-alkoxycoumarins with C60 proceeded stereoselectively under photoirradiation conditions to produce a new class of fullerene fused oligocyclic cyclobutane products. This reaction seems to progress via radical ion pair intermediates that arise from the SET processing of 3-alkoxycoumarins with the excited form of C60.
Keywords: [2+2] cycloaddition; 3-alkoxycoumarin; fullerene; photoreactions; oligocyclic cyclobutane